3‐13 GHz Q‐enhanced low noise amplifier with optimized inductors utilizing in‐phase current returning path technique. Issue 7 (4th March 2019) - Wang, Keping; Yang, Geliang; Wang, Zhigong
Abstract: In this letter, a 3‐13 GHz UWB low noise amplifier (LNA) with high power gain is reported using a standard 130‐nm CMOS. In the first stage, Q‐enhanced inductors are proposed by using an in‐phase current returning path (CRP) technique. Compared to traditional ground ring CRP and anti‐phase CRP, the quality factor of the inductor is improved by decreasing the mutual inductance between the spiral coil and CRP. As a result, the proposed LNA achieves a power gain (S21 ) of 22.5 ± 1.5 dB from 3.4 to 13.2 GHz while combining with the inductive peaking technology. In addition, an average noise figure of 3 dB is achieved within an ultra‐wide band up to 17 GHz. The UWB amplifier also achieves an in‐band IIP3 of −16.8 dBm and a DC power of 20.5 mW at 1.2 V supply. It occupies an area of 0.82 × 0.71 mm 2 including pads.